Clonal hematopoiesis is associated with distinct rheumatoid arthritis phenotypes - Hiitol,a Emil; Korhonen, Juuso; Kokkonen, Heidi; Koskela, Jukka; Kankainen, Matti; Alakuijala, Milla; Liu, Aoxing; Lundgren, Sofie; Häppölä, Paavo; Almusa, Henrikki; Ellonen, Pekka; Savola, Paula; et al. (American Association for the Advancement of Science (AAAS), 2025)
Clonal hematopoiesis (CH) becomes more prevalent with aging and may influence inflammatory diseases by altering immune function. While CH of indeterminate potential (CHIP) promotes inflammation in nonmalignant conditions, its relationship with rheumatoid arthritis (RA) remains unknown. We analyzed CHIP mutations in RA using two population-level cohorts and patients with newly diagnosed RA. CHIP was associated with prevalent RA in 10,089 FINRISK study participants with whole-exome sequencing (OR, 2.06; P = 0.029) and in the FinnGen cohort (n = 520,210; OR, 1.49; P < 0.001) using single-nucleotide polymorphism array-based CHIP annotation. In FinnGen, CHIP was also associated with inferior overall survival in participants with RA (P = 0.013). In newly diagnosed RA (n = 573), DNMT3A-mutated seropositive patients had increased inflammatory markers and disease activity compared with patients without CHIP. In contrast, TET2 mutations were enriched in seronegative RA (P = 0.009). Our findings provide further evidence for the context-dependent association between CHIP and inflammation, with potential therapeutic implications.